2019
DOI: 10.1177/1071100719849850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Syndesmosis Reduction on CT Scan

Abstract: Background: Computed tomography (CT) imaging has traditionally been considered the gold standard for evaluation of syndesmostic reduction, but there is no uniformly accepted method to assess reduction. The aim of this study was to evaluate the intra- and interobserver reliability of published measurement techniques for evaluation of syndesmotic reduction on weightbearing CT scan (WBCT) in hopes of determining which method is best. Methods: Medical records were reviewed to identify patients who underwent operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 28 publications
0
44
0
Order By: Relevance
“…Recent studies have suggested that WBCT may play a more useful role in diagnosing patients with subtle syndesmotic instability by virtue of its ability to visualize the distal syndesmosis cross-sectionally and under physiologic load. 1,2,4,7,9,13,17 This study found that measuring the volume of the syndesmotic joint on WBCT and comparing this measurement with the contralateral uninjured side is an effective method to detect syndesmotic instability. Compared with the contralateral uninjured side, 3D WBCT volume measurements were increased at the injured side among patients diagnosed with arthroscopically confirmed syndesmotic instability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested that WBCT may play a more useful role in diagnosing patients with subtle syndesmotic instability by virtue of its ability to visualize the distal syndesmosis cross-sectionally and under physiologic load. 1,2,4,7,9,13,17 This study found that measuring the volume of the syndesmotic joint on WBCT and comparing this measurement with the contralateral uninjured side is an effective method to detect syndesmotic instability. Compared with the contralateral uninjured side, 3D WBCT volume measurements were increased at the injured side among patients diagnosed with arthroscopically confirmed syndesmotic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that WBCT may play a more useful role in diagnosing patients with subtle syndesmotic instability by virtue of its ability to visualize the distal syndesmosis cross-sectionally and under physiologic load. 1,2,4,7,9,13,17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 3 different measurement methods are necessary to record the relevant criteria of translation medial / lateral, anterior / posterior and fibular rotation. In particular, the sole qualitative side-by-side comparison without measurement data collection shows a very low level of intra-and interobserver reliability and should not be used as an assessment parameter [33].…”
Section: Discussionmentioning
confidence: 99%
“…At least 3 different measurement methods are necessary to record the relevant criteria of translation medial / lateral, anterior / posterior and bular rotation. In particular, the sole qualitative side-by-side comparison without measurement data collection shows a very low level of intra-and interobserver reliability and should not be used as an assessment parameter [33].…”
Section: Davidovitch Et Al Compared the Conventional Versus 3d Scan mentioning
confidence: 99%